Investigation of Conservatory Students’ Perceptions of Value in Terms of Different Variables - MALKOÇ, TÜLÜN (My University, 2022)
There are various factors that affect people's perceptions, attitudes, and behaviours. One of these factors is the values that individuals have. Human values are widely being used as a notion in many disciplines. The aim of this study was to investigate the human values of conservatory students. The research group consisted of 204 conservatory students at the Dicle University State Conservatory and Gaziantep University Turkish Music Conservatory enrolled in the 2019-2020 academic year. In this study, the data of the research were used with a personal information form and the “The Human Values Scale” developed by Dilmaç, Arıcak & Cesur (2014). The data obtained were analysed with the SPSS 22 program. Descriptive analysis, Independent Group ttest, One-Way Analysis of Variance (ANOVA), Pearson Correlation Coefficient were used in quantitative data analysis. The findings showed that with respect to gender, a significant difference was not found in conservatory students’ human values by t-test result. According to the findings, conservatory students’ most important values are human dignity, social, freedom and futuwwat & courage. On the other hand, conservatory students’ the least important values are materialistic. Similarly, according to the variables of age and departments, significant differences were not found in conservatory students’ human values as shown by ANOVA test. Relationships among the subdimensions of the values scale has been determined statistically significant and strong except from between the human dignity and romantic values sub-dimension and between the materialistic values and futuwwat & courage sub-dimensions. It has been observed that participating students’ human values are above the average. This information reveals that conservatory students’ human values are at superior level. Keywords: human values, conservatory students, music students.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Bilim, Teknoloji ve Toplum; Eğitim; Social Sciences and Humanities; Sociology; Science, Technology and Society; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; General Social Sciences; Social Sciences & Humanities; conservatory students; human values; music students